Study Of Total Suspended Solid (TSS) Reduction In Coal Mine Water Management In Block III Of PT. Antang Gunung Meratus, South Tapin District, Tapin Regency, South Kalimantan Province - Azhari, Putri Sari; Rande, Shilvyanora Aprilia; Arie Adnyano, A.A. Inung (Journal of Applied Sciences, Management and Engineering Technology, 2023)
PT. Antang Gunung Meratus is a coal mining company with an area of 22,433 Ha with open pit mining method. PT. Antang Gunung Meratus has been equipped with a wastewater treatment system using active control methods, where  the pH, Fe, Mn and Cd content of mine water is normal while  the total suspended solid (TSS) value is more than 200 ppm in a state exceeding the water quality standard limit set by South Kalimantan Governor Regulation No.36 of 2008. The purpose of this study is to determine the results of water quality before and after it is managed and what methods are used in its management and how much costs are spent in managing the mine water. The research methods used are literature study methods, research in the field, primary and secondary data collection, data processing, data analysis and conclusions. The results showed that mining water in the WWTP area had the  highest total suspended solid (TSS) content  in July 2022 reaching 4.788  mg/l, while at the outlet the total suspended solid (TSS) value was 23 mg/l, the pH value was 7.22. Iron content (Fe) of 0.04 mg / l manganese content (Mn) of 0.006 and Cadmium (Cd) content of 0.004 mg / l, the content in the outlet comes from laboratory tests and costs incurred in mine water management worth Rp. 840,854,400 as of July 2022.